Psychological First-Aid for Santri: Upaya Penguatan Layanan Bimbingan Konseling Dasar untuk Unit Pendidikan di Pondok Pesantren Darussalam Blokagung - Sa'diah, Halimatus; Masnida; Ahmad Syamsul Mu'arif; Ana Ayuning Tyas (Universitas KH. Mukhtar Syafaat (UIMSYA), 2024)
A psychologically comfortable atmosphere in schools and Islamic boarding schools needs to always be sought. Moreover, the Darussalam Islamic Boarding School has thousands of students. One of the obstacles currently being faced is the insufficient quantity of guidance and counseling implementers or counselors, especially regarding their quality. Focusing on improving counseling services provided by guidance and counseling teachers and homeroom teachers, we help improve skills in providing psychological first aid to students or students who experience psychological instability. We offer training with the concept of Psychological First-aid (PFA), which is a series of actions or things that must be done to help strengthen the mentality of someone who is experiencing a crisis or unstable condition. The technique used is Appreciative Inquiry in Asset Based Community Development. As a result, homeroom teachers and guidance and counseling teachers understand the importance of psychological assistance and a series of actions provided to help strengthen the mental health of santri/students who are experiencing a crisis or unstable condition. Guidance and guidance teachers and homeroom teachers also understand the sequence of steps that must be taken when providing assistance.